Strolling the Coastline: Criminology in Everyday Life: Through ‘Landscape’ from Gaol to ‘Badlands’ - D. Brown (Law Text Culture, 2009)
Part travelogue, part flight of fancy, this paper recounts a coastline stroll from Maroubra Beach to Bondi in Sydney’s eastern suburbs. The author as ‘travel guide’ points out features of potential interest to two visiting criminological colleagues as they ‘pass by’ scenery of great beauty shadowed by acts of spectacular violence. The everyday acts of walking and talking while passing through a ‘landscape’ serve to constitute a criminology of everyday life, illustrating the way in which a consciousness of crime, crime sites, analyses and theories permeates the ways a ‘tourist trail’ might be experienced and seen, myths made and histories forged. The walk starts with the unseen lines of penal force radiating from Long Bay Gaol, before skirting through surfing and its regulation; the ‘brotherhood’ of the BRA Boys; the Hines killing and the politics of self defence; the shark arm case, the Virgin Mary and the Bali bombing memorial at Coogee; zones of the beach and Jock Young’s Vertigo at Bronte and Tamarama; before finishing at the Marks Park ‘badlands’ at Bondi, scene of a series of mostly unsolved and unpunished homophobic killings, giving rise to reflections on ‘ungrievable lives’, memory, mourning and forgetting.